Construction of orthonormal wavelet-like bases - Morillas, Patricia Mariela (2010)
A general method for constructing wavelet-like bases in a Hilbert space H starting from any orthonormal basis in H and any periodic orthonormal wavelet basis is presented. With this method we can take advantage of the characteristics of both types of bases to obtain orthonormal wavelet-like bases that are suitable to represent functions and operators efficiently.